The impact of shopping attributes and online shopping experience on customer loyalty with satisfaction as a mediation in the e-commerce shopee - Pitta Tresia Simangunsong; Romindo Pasaribu; Jusmer Sihotang; Frederick Saroha Silaban (Trigin Publisher, 2023)
Along with the rise of internet users and digital applications, e-commerce has begun to attract many people. One of the marketplace applications that is currently being used is Shopee. Shopee is one of many parties taking advantage of e-commerce business opportunities by enlivening the mobile marketplace segment through their mobile application to facilitate buying and selling transactions via mobile devices. Loyalty is a measure of how likely customers will switch to other e-commerce. For this reason, company management is needed so that they can determine the marketing strategy that will be used in the future appropriately. Furthermore, the satisfaction variable is used as a mediating variable to increase consumer loyalty to the use of shopee. Data collection was carried out online through the Google Forms model with 200 available respondents. Structural Equation Modeling (SEM) analysis is used to test the measurement and structural models through Smart-PLS 3.0. The results of this study indicate that the 7 hypotheses are accepted which proves that all hypotheses have a positive and significant effect on each other.